Mediation Job Satisfaction: Transformational Leadership, Internal Communication and Organizational Culture to Increase Employee Engagement - Ramadhi, Ramadhi; Sarianti, Kiki; Desti, Yolanda (Journal of Business Management and Economic Development, 2023)
This study aims to determine how much influence transformational leadership, internal communication and organizational culture have on employee engagement through job satisfaction as an intervening variable at Sijunjung Hospital. This research study uses quantitative analysis with a total sample of 11 employees. The sampling technique in this study is by census, namely the entire population is a sample of 114 employees of Sijunjung Hospital. The validity and reliability of the outer model were assessed through SmartPLS analysis, while the smartPLS inner model was used to test hypotheses. The results obtained based on the Partial Test (t test) obtained: a) there is no significant effect of transformational leadership on job satisfaction, b) there is a significant influence of internal communication on job satisfaction, c) there is a significant influence of organizational culture on job satisfaction, d) there is significant effect of transformational leadership on employee engagement, e) there is a significant effect of internal communication on employee engagement, f) significant effect of job satisfaction on employee engagement, g) job satisfaction cannot mediate the effect of transformational leadership on employee engagement, h) job satisfaction can mediate the effect internal communication on employee engagement, f) job satisfaction can mediate the influence of organizational culture on employee engagement